Short stories in the academy: Mimesis, diegesis and the role of drama and film. Issue 1 (1st December 2012) - Neale, Derek
The new prominence of authors teaching Creative Writing in the academy might have seemed unlikely given a critical context that railed against the influence of authors in interpretation. This discussion suggests reasons for an unlikely coalescence between theory and practice, and considers how situating the study of writing within the academy might have affected the short form, giving rise to more mimetic, less diegetic types of story and certain fashions in narrative style, ones often related to drama and film. The discussion considers the workshop vogue for the second person narrative, examining a story by Lorrie Moore; it investigates filmic influences including Sergei Eisenstein's theories of montage; and compares two versions of a story by Raymond Carver story.